Evolução e análise funcional de uma domus romana. A unidade habitacional da zona arqueológica das “antigas Cavalariças” de Braga - Silva, Juliana Ferreira da (2015)
This work aims to give notice of the characteristics and evolution of a Roman domus in Bracara Augusta city, based on the results of the excavations conducted by the Unit of Archaeology at the University of Minho in the archaeological area of ‘Antigas Cavalariças de Braga’. The plentiful of data resulting from the excavations allowed to functionally analyze some of the domus spaces that have been described in accordance with its architectural evolution, between the flavian period and Late Antiquity. As a result different planimetric proposals for the various phases of the building are discussed and it is expected to contribute to a better understanding the Roman domestic architecture in Bracara Augusta.